Development and validation of a tool to evaluate Inpatient Beliefs, Expectations and Attitudes toward Reflexology (IBEAR-16). (April 2018) - Attias, Samuel; Schiff, Elad; Arnon, Zahi; Ben-Arye, Eran; Keshet, Yael; Sroka, Gideon; Matter, Ibrahim; Boker, Lital Keinan
Abstract: Background: The integration of manual therapies, including reflexology, into conventional care settings is growing extensively. Patients' beliefs, attitudes and expectations toward these therapies interact with their outcomes, but currently there are no validated tools to evaluate these factors. We aimed to design and to validate such a tool specifically targeted into reflexology. Methods: Following input of a multidisciplinary team of experts, the self-administered Inpatient Beliefs, Expectations and Attitudes toward Reflexology (IBEAR) questionnaire was constructed, containing 25 items, 8 referring to demographics and 17 specifically addressing reflexology. Cronbach's alpha was computed to evaluate the questionnaire's internal reliability, and factor analysis was used for further validation (232 patients). Pearson coefficient and Kappa tests were used to test and retest (within 48 hours) the questionnaire on a group of 199 patients, to assure clarity and reliability. Results: For the 232 questionnaires collected, the computed Cronbach's alpha coefficient was 0.716 (acceptable reliability). Factor analysis pointed to two content areas separated into four items addressing attitudes and expectations and five items focusing on beliefs and attitudes. In the test-retest stage, 199 participants filled in the questionnaire for a second time. The Pearson coefficient for all questions ranged between 0.73 and 0.94 (good to excellent correlation) and Kappa scores ranged between 0.66 and 1.0 (moderate to high reliability). Consequently, one of the questions was removed from the IBEAR. Conclusions: The present study provides evidence that the proposed IBEAR questionnaire with 16 items is a valid and reliable tool for evaluation of inpatients' beliefs, expectations and attitudes toward reflexology.